Mathematical model of mechanical subsystem of traction electric drive of an electric locomotive - Goolak, S.; Sapronova, S.; Tkachenko, V.; Riabov, Ie.; Overianova, L.; Yeritsyan, B. (Volodymyr Dahl East Ukrainian National University, 2021)
The mathematical model of the mechanical subsystem of the traction electric drive of the four-axle section of the locomotive is developed in the article. The peculiarity of the model is taking into account the interconnected vertical oscillations of the locomotive and torsional oscillations in traction transmission and the influence of the anti-discharge device on the processes in the traction electric drive. This allows taking into account the relationship of oscillations of the crew of the locomotive, which have a significant impact on the processes in the electrical part of the traction drive. The model describes the oscillations of the locomotive body, two carts, four wheel pairs, traction motors and gearboxes. When developing the model, the assumption of linear dependence of stiffness and damping coefficients on displacements and velocities is accepted. Coupling of a wheel with a rail is described by means of the approximated dependence. The oscillations of the rails and the bases of the rail track are introduced into the model. As perturbation for vertical oscillations the roughness of a rail track is accepted. The model takes into account the influence of traction force and vertical oscillations of the crew on the unloading of the axles of the locomotive. This will allow us to study the processes of realization of the locomotive's maximum traction forces in the traction mode and in the mode of electrodynamics braking. The use of the developed mathematical model of the mechanical subsystem will allow taking more fully into account the mutual influence of electrical processes and mechanical oscillations on each other, which will increase the accuracy of modeling. The model can be used for research of freight electric locomotives such as VL10, VL11, VL82, VL80, 2EL4, 2EL5 in order to further improve their traction electric drives, in particular, to determine the rational modes of application of the anti-unloading device in traction and braking modes. Further application of the mathematical model is possible to assess the performance of the traction drive and the locomotive in general in the study of modern traction drives, in particular, asynchronous, the use of which is possible on the above locomotives.

У статті розроблено математичну модель механічної підсистеми тягового електроприводу чотирьохвісної секції локомотиву. Особливістю моделі є врахування взаємопов'язаних вертикальних коливань локомотива і крутильних коливань у тягової передачі та впливу роботи протирозвантажувального пристрою на процеси в тяговому електроприводі. Це дозволяє врахувати взаємозв’язок коливань екіпажної частини локомотиву, які мають значущий вплив на процеси в електричній частині тягового електроприводу. Модель описує коливання кузова локомотиву, двох візків, чотирьох колісних пар, тягових двигунів та редукторів. При розробці моделі прийнято припущення про лінійну залежність коефіцієнтів жорсткості та демпфування від переміщень та швидкостей. Зчеплення колеса з рейкою описано за допомогою апроксимованої залежності. У модель введено коливання рейок та основи рейкової колії. У якості збурення для вертикальних коливань приймається нерівність рейкової колії. У моделі враховано вплив сили тяги і вертикальних коливань екіпажу на розвантаження осей локомотива. Це дозволить досліджувати процеси при реалізація локомотивом граничних тягових зусиль у тяговому режимі та у режимі електродинамічного гальмування. Використання розробленої математичної моделі механічної підсистеми дозволить більш повно врахувати взаємний вплив електричних процесів і механічних коливань один на одного, що підвищить точність моделювання. Модель може бути застосовано для досліджень вантажних електровозів типу ВЛ10, ВЛ11, ВЛ82, ВЛ80, 2ЕЛ4, 2ЕЛ5 з метою подальшого удосконалення їх тягових електроприводів, зокрема, визначенню раціональних режимів застосування протирозвантажувального пристрою у тягових та гальмівних режимах. Подальше застосування математичної моделі можливе для оцінки показників тягового електроприводу і локомотиву в цілому при дослідженні сучасних тягових електроприводів, зокрема, асинхронного, застосування яких можливе на вищезазначених локомотивах.
Keywords: electric locomotive; traction electric drive; bogie; oscillation; електровоз; тяговий електропривод; візок; коливання